UPAYA PERAN BHABINKAMTIBMAS MELALUI BIMBINGAN PENYULUHAN GUNA MENCEGAH PENCURIAN KENDARAAN BERMOTOR DI POLRES PATI - PANDE MADE RAMA KRISNANANDA PANDE (Indonesian Journal of Police Studies, 2022)
ABSTRACT EFFORTS TO INCREASE THE ROLE OF BHABINKAMTIBMAS THROUGH COUNSELING GUIDANCE TO PREVENT MOTOR VEHICLE THEFT AT PATI POLRES Pande Made Rama Krisnananda, 18.178, panderama18@gmail.com This research is motivated by the case of motor vehicle theft which has always been the case with the highest number for the last three years at the Pati Police. The Pati Police apply the counseling guidance method by the Bhabinkamtibmas Unit to prevent motor vehicle theft. The purpose of this research is to know the implementation of the Bhabinkamtibmas Unit to prevent motor vehicle theft, the factors, and efforts to increase the role of the Bhabinkamtibmas Unit to prevent the crime of motor vehicle theft. Theories and concepts used in this research are management theory, POAC theory, Bhabinkamtibmas concept and counseling guidance concept. This study uses a qualitative approach with the type of field research and is supported by data collection through interviews, observation and document review. Based on the results of the study, the authors found the fact that the Bhabinkamtibmas Unit of the Pati Police had not been able to adjust the planning, implementation and organization stages contained in the National Police Chief Regulation Number 21 of 2007 concerning Guidance and Counseling on Security and Public Order, so that the performance of the Bhabinkamtibmas Unit was not optimal. The implementation of counseling guidance carried out by the Bhabinkamtibmas Unit is influenced by internal factors and external factors. The Pati Police carried out efforts to increase the role of the implementation of counseling guidance through the 6m element of management theory. With the results of the research, the authors provide suggestions and input to the Bhabinkamtibmas Unit in carrying out counseling guidance to optimize at the planning, organizing and implementation stages so that the results of the implementation are optimal.